Suicide Rate in Republic of Srpska - Bojanić, Nebojša; Srdanović, Marko; Marinković, Darko (Kriminalističke teme, 2016)
Reason(s) for writing and research problem(s): Suicide rate is a “tool” used to measure how serious the problem of suicide really is in a certain area at a certain time. Suicide is a very complicated matter, It can be a consequence of a criminal act, but it can also be caused by a physical or mental illness. Suicide itself also leaves some consequences such as, grief, pain, loss of friends and family, orphaned children, etc. The Subject of work here is the suicide rate in Republic of Srpska and how it compares to the suicide rates in District Brčko, Fedaration of Bosnia and Herzegovina and in the entire Bosnia and Herzegovina. Aims of the paper (scientific and/or social): The aim of this work is a scientific description and explaination how the suicide rate has changed in Republic of Srpska from 2007. to 2011. Methodology/Design: Statistical methods were used to process official data from the Republic of Srpska Institute of Statistics, Federal Institute of Statistics, Bosnia and Herzegovina Institute of Statistics, The Republic of Srpska Ministry of Interior, Federal Ministry of Interior, Police of District Brčko and other agencies like the World Health Organization. Data was gathered by a survey and analyzed was with the use of descriptive and inferential statistics and classification. For testing certain hypotheses, Chi-squared test was used. Research/paper limitations: This research was an integral part of a larger research into suicide rates in Bosnia and Hercegovina. Also this research covered suicides in Bosnia and Hercegovina from 2007. to 2011. Results/Findings: Based on population estimates, both at the level of Bosnia and Herzegovina and at the entity level, and the research conducted, it was information that the suicide rate in the Republic of Srpska medium height, with an alarming increase in the indicators. General conclusion: The suicide rate in the Republic of Serbian is higher than the rate of suicides in the Federation of Bosnia and Herzegovina Research/paper validity: Depending on the circumstances of how the suicide was carried out, the state can try to influence and lower the suicide rate. And that is important because suicide is not an isolated act.